Situação epidemiológica da brucelose bovina e caracterização da pecuária bovina no estado de Minas Gerais, 2011. - Luciana Faria de Oliveira (2016)
This cross-sectional study was conducted in the state of Minas Gerais, Brazil, in 2011 to estimate the seroprevalence of bovine brucellosis (Brucella abortus) in properties and cattle, and to identify potential infection risk factors for herds with cows of reproductive age. The state was divided into seven regions: 1. Noroeste, Norte and Nordeste; 2. Leste; 3. Central; 4. Zona da Mata; 5. Sul and Sudoeste; 6. Alto Paranaíba; and 7. Triângulo Mineiro. Random, two-stage sampling was performed of both properties and cattle from each property. Blood samples were collected from 18,990 cows of reproductive age from 2,185 properties. The serologic tests used for the detection of anti-B. abortus antibodies included the buffered, acidified plate antigen test, as a screening test, with the 2-mercaptoethanol reduction, test as a confirmatory test, as recommended by the Programa Nacional de Controle e Erradicação da Brucelose e Tuberculose Animal - PNCEBT (National Program for the Control and Eradication of Animal Brucellosis and Tuberculosis). The seroprevalence of bovine brucellosis on the surveyed properties and in cattle were 3.59% (95% confidence interval [CI]: 2.76 4.42%) and 0.81% (95% CI: 0.05-1.10%), respectively. Multiple logistic regression analysis identified the total number of cows in the property as a risk factor for the presence of anti-B. abortus antibodies, with an odds ratio (OR) of 1.93 (95% CI: 1.12 - 3.34) for herds with 30 to 210 cows and 7.81 (95% CI: 3.72-16.38) for those with more than 210 cows, relative to the risk in herds with less than 30 cows, the base category. While these results demonstrate a significant reduction in the prevalence of properties with bovine brucellosis, the disease is still present in Minas Gerais, with properties with higher numbers of cows at higher risk for infection.